Difficulties in the differential diagnosis of erythema nodosum: Primary myelofibrosis as an etiological factor - D. I. Abdulganieva; I. F. Fayrushina; E. V. Sukhorukova; I. L. Serdyuk; M. A. Kunst; R. Z. Abdrakipov; M. A. Afanasyeva (Современная ревматология)
Erythema nodosum (EN) is the most common form of panniculitis that is a reactive process caused by a wide variety of etiological factors. The problems with the differential diagnosis of this abnormality have not lost its relevance. The paper deals with a clinical case of recurrent EN concurrent with an immunological phenomenon (positivity for rheumatoid factor and antimitochondrial antibodies), long-lasting asymptomatic splenomegaly, and subsequently developed primary myelofibrosis. To ascertain the cause of secondary EN often causes difficulties in real clinical practice.